Mapping Sustainable Bilingual Digital Innovation through University–Local Government Collaboration in Tourism Education - Arjulayana, Arjulayana; Khazinatul Khaeriah, RD. Hera Merdeka; Lastari, Dyah Supraba; Adawiyah, Rabiatul; Pujiati, Tri (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: The rapid development of digital technology in the tourism sector needs to be balanced with the provision of globally accessible information by bilingual languages, particularly Indonesian and English. This study aims to examine the importance of sustainable bilingual digital information in tourism education, supported by collaboration between universities and local governments. Method : This study uses a mixed-method with convergent parallel design.Data collection techniques in the form of observation and semi-structured interviews. The research subjects consisted of 62 respondents, including government officials staff, language lecturers, teachers, and the community of bilingual digital applications user . Results: The results show 83% respondens stated that bilingual digital applications, such as Tangerang Gemilang application contributes significantly to increase the effectiveness of tourism promotion and expand access to information for users. In addition, collabora-tion between universities and tourism agencies is considered crucial in supporting comprehensive and internationally oriented local tourism development. Novelty: This study confirms that sustainable bilingual digi-tal innovation, through institutional synergy, has a strategic role in strengthening tourism education and the competitiveness of tourist destinations.